Factors influencing scholarly publication productivity: a systematic review. Issue 1 (25th February 2021) - Wahid, Nazia; Warraich, Nosheen Fatima; Tahira, Muzammil
Abstract : Purpose: The importance of scientific publications has enhanced the research activities at all aggregate levels. The purpose of this paper is to conduct an in-depth review of studies examined the factors that influence the publication productivity among researchers, institutions and countries. Design/methodology/approach: This paper uses a systematic literature review approach that is based on relevant literature retrieved from two authentic and well-known databases named Web of Science and SCOPUS. Kitchenham protocol of systematic review was applied, and relevant studies were searched by selected keywords search. Inclusion and exclusion criteria were used to select high quality studies. A rigorous study selection procedure was designed. Findings: Findings reveal that several factors play a significant role in the publication productivity growth. All of the identified factors were grouped into three categories. Most of the factors belong to personal category while two top dominant factors, funding and collaboration fall into situational category. Other most influential factors, time, academic rank and academic qualification are personal. Findings highlight that publication output at individual level is strongly influenced by personal factors while few environmental and situational factors also affect the number of publications. Publication productivity of institutes and countries is affected by environmental and situational factors. Originality/value: This paper contributes by providing a detailed review to explore the influencing factors of scholarly publication of researchers, institutions and countries. This study will be supportive for researchers and policymakers for making strategies to stimulate the research publication practices at researchers, institutions and national level.